Recurring basal cell carcinoma involving exclusively intra-oral mucosa: a case report - Siqueira, Juliana Mota; Nunes, Julia Puglia; Guaita, Henrique Pereira; Melo, Gabriela Banacu de; Nunes, Fabio Daumas; Gallo, Camila de Barros (Journal of Oral Diagnosis, 2024)
Basal cell carcinoma (BCC) is the most common skin cancer, but oral involvement is extremely rare. Here, we showed a case of a 71-year-old Caucasian male patient presenting an asymptomatic submucosal nodule in the left buccal mucosa on the same side of a previous BCC skin lesion. Intraoral examination revealed a circumscribed sessile and fibrous mass covered by normal mucosa. An incisional biopsy was performed. Microscopically, the lesion showed uniform, ovoid, dark-staining basaloid cells with medium-sized nuclei and little cytoplasm arranged in islands and strands, invading the underlying connective tissue. These islands demonstrated palisading of the peripheral cells and occasionally central areas with epidermoid differentiation. The final diagnosis was nodular basal cell carcinoma. Although uncommon, recurrent BCC may occur in the oral cavity.